2022
DOI: 10.3390/jpm12030494
|View full text |Cite
|
Sign up to set email alerts
|

Neoexpression of JUNO in Oral Tumors Is Accompanied with the Complete Suppression of Four Other Genes and Suggests the Application of New Biomarker Tools

Abstract: Background. Our study describes the neoexpression (Juno) and suppression (catsperD, dysferlin, Fer1L5 and otoferlin) of selected genes in oral squamous cell carcinomas (OSCCs). As the expression pattern of these genes allows a “yes” or “no” statement by exhibiting an inverse expression pattern in malignant versus benign tissues, they represent potential biomarkers for the characterization of oral malignancies, particularly OSCCs. Methods. Differential expression analyses of selected genes of interest were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In clear cell renal cell carcinoma, Cox et al (2021) showed in a study of 79 patients that otoferlin was an indicator of tumor staging and a prognostic biomarker for cancer-specific survival. In 25 patients with oral squamous cell carcinoma, Kraus showed complete suppression of otoferlin expression in malignant tissue ( Kraus et al, 2022 ). Taken together, these results suggest a role for otoferlin in the carcinogenesis of these tumors, which deserves investigation to confirm and understand its exact role, especially as it appears to vary according to tumor site.…”
Section: Otoferlin and Cancermentioning
confidence: 99%
“…In clear cell renal cell carcinoma, Cox et al (2021) showed in a study of 79 patients that otoferlin was an indicator of tumor staging and a prognostic biomarker for cancer-specific survival. In 25 patients with oral squamous cell carcinoma, Kraus showed complete suppression of otoferlin expression in malignant tissue ( Kraus et al, 2022 ). Taken together, these results suggest a role for otoferlin in the carcinogenesis of these tumors, which deserves investigation to confirm and understand its exact role, especially as it appears to vary according to tumor site.…”
Section: Otoferlin and Cancermentioning
confidence: 99%